Step
*
2
1
of Lemma
imonomial-cons
1. u : ℤ
2. v : ℤ List
3. ∀u,a:ℤ. ∀f:ℤ ⟶ ℤ.  (int_term_value(f;imonomial-term(<a, [u / v]>)) = int_term_value(f;imonomial-term(<a * (f u), v>)\000C) ∈ ℤ)
4. u@0 : ℤ
5. a : ℤ
6. f : ℤ ⟶ ℤ
⊢ int_term_value(f;imonomial-term(<a, [u@0; [u / v]]>)) = int_term_value(f;imonomial-term(<a * (f u@0), [u / v]>)) ∈ ℤ
BY
{ (InstHyp [⌜u⌝;⌜a * (f u@0)⌝;⌜f⌝] 3⋅ THENA Auto) }
1
1. u : ℤ
2. v : ℤ List
3. ∀u,a:ℤ. ∀f:ℤ ⟶ ℤ.  (int_term_value(f;imonomial-term(<a, [u / v]>)) = int_term_value(f;imonomial-term(<a * (f u), v>)\000C) ∈ ℤ)
4. u@0 : ℤ
5. a : ℤ
6. f : ℤ ⟶ ℤ
7. int_term_value(f;imonomial-term(<a * (f u@0), [u / v]>)) = int_term_value(f;imonomial-term(<(a * (f u@0)) * (f u), v>\000C)) ∈ ℤ
⊢ int_term_value(f;imonomial-term(<a, [u@0; [u / v]]>)) = int_term_value(f;imonomial-term(<a * (f u@0), [u / v]>)) ∈ ℤ
Latex:
Latex:
1.  u  :  \mBbbZ{}
2.  v  :  \mBbbZ{}  List
3.  \mforall{}u,a:\mBbbZ{}.  \mforall{}f:\mBbbZ{}  {}\mrightarrow{}  \mBbbZ{}.    (int\_term\_value(f;imonomial-term(<a,  [u  /  v]>))  =  int\_term\_value(f;imonomial-\000Cterm(<a  *  (f  u),  v>)))
4.  u@0  :  \mBbbZ{}
5.  a  :  \mBbbZ{}
6.  f  :  \mBbbZ{}  {}\mrightarrow{}  \mBbbZ{}
\mvdash{}  int\_term\_value(f;imonomial-term(<a,  [u@0;  [u  /  v]]>))  =  int\_term\_value(f;imonomial-term(<a  *  (f  u@\000C0),  [u  /  v]>))
By
Latex:
(InstHyp  [\mkleeneopen{}u\mkleeneclose{};\mkleeneopen{}a  *  (f  u@0)\mkleeneclose{};\mkleeneopen{}f\mkleeneclose{}]  3\mcdot{}  THENA  Auto)
Home
Index